2022
DOI: 10.1186/s12876-022-02245-6
|View full text |Cite
|
Sign up to set email alerts
|

Peptic ulcer disease among dyspeptic patients at endoscopy unit, University of Gondar hospital, Northwest Ethiopia

Abstract: Background Dyspepsia is a common complaint in upper gastrointestinal disorders. It is described as predominant epigastric pain lasting for at least one month. Globally, peptic ulcer disease occurs in 3.5–32% of patients with dyspepsia. Helicobacter pylori (H. pylori) infection and non-steroidal anti-inflammatory drugs/aspirin use are the widely known risk factors for peptic ulcer disease. There was no recent document on H. pylori infection rate among patients with peptic ulcer disease in Ethiop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
1
3
0
3
Order By: Relevance
“…Гастроэзофагеальная рефлюксная болезнь, язвенная болезнь желудка и функциональная диспепсия являются наиболее частыми причинами диспепсических симптомов. Лишь в немногих случаях диспепсические симптомы вызваны злокачественными новообразованиями ЖКТ [26][27][28].…”
Section: результатыunclassified
“…Гастроэзофагеальная рефлюксная болезнь, язвенная болезнь желудка и функциональная диспепсия являются наиболее частыми причинами диспепсических симптомов. Лишь в немногих случаях диспепсические симптомы вызваны злокачественными новообразованиями ЖКТ [26][27][28].…”
Section: результатыunclassified
“…В этиопатогенезе ЯБЖ вовлечены множество внешних и внутренних факторов риска (неправильный режим употребления пищи, бесконтрольный прием антибиотиков, индуцирующий выживание самых агрессивных штаммов Helicobacter pylori (Н. pylori), частое применение нестероидных противовоспалительных средств (НПВС), разрушающих защитный слой слизистой оболочки желудка, стрессовый фактор, курение, прием алкоголя и др. ), так и наследственные факторы [4,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. По различным данным, вклад наследственности в этиопатогенез заболевания составляет от 5,5 до 50% [29].…”
Section: Introductionunclassified
“…A study showed that 4.4 billion people (57.9% of the global population at that time) were infected with H. pylori in 2017 (11). and global reports show that the prevalence of H. pylori infection in patients with PUD is 14-21% in the United States, 60-70% in Asia, and 70-90% in sub-Saharan Africa (12,13). Therefore, worldwide consensus guidelines recommend mandatory H. pylori eradication in patients with PUD (14).…”
Section: Introductionmentioning
confidence: 99%
“…and global reports show that the prevalence of H . pylori infection in patients with PUD is 14–21% in the United States, 60–70% in Asia, and 70–90% in sub-Saharan Africa ( 12 , 13 ). Therefore, worldwide consensus guidelines recommend mandatory H .…”
Section: Introductionmentioning
confidence: 99%